Culture and learning : access and opportunity in the classroom - Olssen, Mark (International perspectives on curriculum., 2004)
Twenty-seven academics from the UK, U.S., and New Zealand contribute 18 essays on the impact of social structure on educational learning, educational access, and opportunity and outcomes, in an effort to renew the debate concerning the sociology of school attainment.